2012
DOI: 10.1002/ep.11656
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organic dyes removal mechanism in electrocoagulation process using iron and aluminum anodes

Abstract: The removal of Reactive red 43, as a model pollutant, and some organic dyes with different structures by electrocoagulation process was investigated using iron (EC‐Fe) and aluminum (EC‐Al) anodes to explain dyes removal mechanism differences in EC‐Fe and EC‐Al processes. First, the effects of current density, electrolysis time and pH on the removal of Reactive Red 43were studied. The maximum removal efficiency (RE) was obtained in relatively acidic medium (pH = 4.25) in the first 12 minutes of EC‐Al. While, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…3. Similar fits of second-order kinetics were obtained by Bener et al [11] and Amani-Ghadim et al [44].…”
Section: Analysis Of During and After Process Variablessupporting
confidence: 85%
“…3. Similar fits of second-order kinetics were obtained by Bener et al [11] and Amani-Ghadim et al [44].…”
Section: Analysis Of During and After Process Variablessupporting
confidence: 85%
“…In the recent years, various processes such as biological methods , adsorption , chemical coagulation , ion exchange , membrane filtration , photocatalysis , oxidation , and electrocoagulation (EC) have been used for the treatment of azo dye‐containing wastewaters. EC treatment process has been gaining popularity in the treatment of wastewaters containing azo dyes because of providing a simple, reliable, and cost‐effective procedure [, ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that NaCl plays an important role in electrochemical oxidation through the destruction of dye molecules via the action of generated hypochlorous acid (HOCl) and hypochlorite ion (OCl 2 ) in the solution (Eqs. [1][2][3][4][5], which ensures an indirect electrochemical oxidation process [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is clear that effluents containing reactive azo dyes need to be appropriately treated before being discharged into the environment . However, because of the aforementioned problems, it is not easy in terms of removal efficiency and economic burden to handle these compounds with conventional physicochemical and biological techniques . For these reasons, for treatment of textile wastewater, the electrochemical oxidation technique using electric fields was first proposed by Lin and Peng ; this method is becoming an attractive alternative and a powerful decolorization and degradation dye molecule technique to replace or improve the existing processes .…”
Section: Introductionmentioning
confidence: 99%